'At home, he's a pet, at work he's a colleague and my right arm': police dogs and the emerging posthumanist agenda. Issue 5 (1st November 2020) - Knight, Charles; Sang, Kate
ABSTRACT: Increased attention is being paid to non-human animals, inspired in part by Human-Animal Studies and theoretical frameworks which reveal the fragility of human/animal dualism. Via the application of posthumanist performativity, we explore the recruitment and careers of police dogs via organisational analysis. It reveals a complex process of a dog becoming a police dog. Police dogs are placed within a speciesist hierarchy where they hold a position of 'good' non-human animals, rather than instrumental tools of the organisation. However, this position is tenuous, with dogs' retirement often resulting in death. The paper concludes by arguing that posthumanist frameworks can be used to decentre the human subject. Contributions of our work include empirical insights on the use of non-human animals in policing coupled with the theoretical application of posthumanism to intersubjectivity in organisations.